Development and testing of an alternative responder definition for EULAR Sjögren's Syndrome Patient Reported Index (ESSPRI). Issue 1 (17th March 2023) - Wratten, Samantha; Abetz-Webb, Linda; Arenson, Ethan; Griffiths, Pip; Bowman, Simon; Hueber, Wolfgang; Ndife, Briana; Kuessner, Daniel; Goswami, Pushpendra
Abstract : Objectives: Dryness, fatigue and joint/muscle pain are typically assessed in Sjögren's trials using European Alliance of Associations for Rheumatology Sjögren's Syndrome Patient Reported Index (ESSPRI). A Patient Acceptable Symptom State of <5 and a Minimal Clinically Important Improvement (MCII)/responder definition (RD) of ≥1 point or 15% on ESSPRI have previously been defined. This study explored alternative RDs to better discriminate between active treatment and placebo in trials. Methods: Anchor-based and distribution-based methods were used to derive RD thresholds in blinded phase IIb trial data (N=190) and confirm these in blinded data pooled from three early phase II trials (N=126). The populations consisted of individuals with moderate-to-severe systemic primary Sjögren's. Anchors were prioritised by ESSPRI correlations and used in similar conditions. Triangulated estimates were discussed with experts (N=3). The revised RD was compared with the original using unblinded data to assess placebo and treatment responder rates. Results: Patients were predominantly female (>90%), white (90%), with mean age of 50 years. Receiver operating characteristic estimates supported an MCII threshold of 1.5–1.6 in the phase II data, whereas correlation-weighted mean change estimates supported a low/minimal symptom severity threshold of ≥2. A low/minimal symptom severity of ≤3 showed the greatest sensitivity/specificity balance. Analyses in the pooled data supported these thresholds (MCII: 1.5–2.1; low/minimal symptom severity: 2.7–3.7). Unblinded analyses confirmed the revised RD reduced placebo rates. Conclusions: Completing a trial with an improvement of ≥1.5 points compared with baseline and an ESSPRI score of ≤3 points is a relevant RD for moderate-to-severe systemic Sjögren's and reduces placebo rates.